Kebijakan Hukum Pidana Dalam Perlindungan Hukum Terhadap Anak Sebagai Korban Pelecehan Seksual Di Kota Pekanbaru Oleh Lembaga Perlindungan Anak Provinsi Riau - Fajar Yuda Utomo; Emilda Firdaus; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Human rights are fundamental rights that are naturally inherent in human beings, is universal, and bestowed by God Almighty. In the protection of human rights, children are also included in it. Child is a person under 18 (eighteen), including children who are still in the womb. Child protection efforts should be initiated as early as possible, but the reality is still often heard children become victims of sexual abuse. In Indonesia there is an independent state agency whose functions do safeguard and improve the welfare of children, the institution in question is the Indonesian Child Protection Agency, while for the Province of Riau Riau Provincial Child Protection Agency. Based on data obtained from LPA Riau province on the issue of child protection in the city of Pekanbaru, many child abuse cases that occur each year, and the most numerous cases are cases of sexual harassment, as well as the number of cases is increasing in the last three years. In this case relates to the settlement of cases of children who are victims of sexual harassment in the city of Pekanbaru by the Child Protection Agency in Riau province. The purpose of this thesis, namely First, Policy Criminal Law In the Legal Protection Against Children As Victims of Sexual Abuse in the city of Pekanbaru by the Child Protection Agency in Riau, Second, obstacles encountered in Legal Protection Against Children As Victims of Sexual Abuse in the city of Pekanbaru by Protection Agency Children's Riau Province, Third, efforts are being made to overcome the obstacles in Legal Protection Against Children As Victims of Sexual Abuse in the city of Pekanbaru by the child Protection Agency in Riau province.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or point studied to provide complete and clear picture of the issues examined. This research was conducted at the Child Protection Agency of Riau province, while the sample population is a whole party with regard to the issues examined in this study, the data source digunakanyakni primary data, secondary data, and the data tertiary, data collection techniques in this study carried out by questionnaires, interviews, and review of the literature.From the research there are three main issues that can be inferred. First, the Child Protection Agency (LPA) Riau Province is an independent state agency in charge of supervising, and resolving cases of violation of children that occurred in the province of Riau. Second, the constraints faced by LPA Riau Province in providing legal protection to children as victims of sexual abuse there are two (2) factors, internal factors and external factors. Third, efforts made by the Child Protection Agency of Riau Province in overcoming obstacles in the legal protection of children as victims of sexual abuse in the city of Pekanbaru has two attempts namely through the preventive and repressive efforts. Suggestions Author, First, in preventing and combating the crime of sexual abuse is expected to continue to do the proper preventive measures such as socialization, workshops, and others. Second, the legal protection of children as victims of sexual abuse committed by LPA Riau province needs to fix the internal factors and external factors.Keywords: Child Protection Agency - Children Victims - Sexual Harassment